Optimization and validation of a procedure using the dried saliva spots approach for the determination of tobacco markers in oral fluid - Marques, Hernâni; Rosado, Tiago; Barroso, Mário; Passarinha, Luis; Gallardo, Eugenia (My University, 2022)
Exposure to tobacco smoke is one of the most common causes of premature death worldwide and is the cause of 8 million deaths annually. We have developed, optimized, and validated a procedure for the detection of nicotine, cotinine and trans-3-hydroxycotinine (biomarkers of tobacco exposure) in oral fluid using the dried saliva spots sampling approach and gas chromatography coupled to tandem mass spectrometry, thus allowing the distinction between active and passive smokers. For optimization, four parameters were evaluated, namely extraction solvent, extraction solvent volume, extraction time and spots drying time. During method validation, the parameters selectivity, linearity, precision and accuracy, recovery, stability, and dilution factor were assessed. Linearity was obtained for all target analytes in the concentration range of 10–200 ng/mL allowing the quantification of compounds up to 1000 ng/mL considering the dilution factor. The method recoveries ranged from 29.2% to 43.30% for nicotine, 66.60–89.10% for cotinine and 80.30–92.80% for trans-3-hydroxycotinine, while achieving intra-day, inter-day and intermediate precision and accuracy values never higher than 10.37% and ±6.62% respectively for all compounds. The herein described analytical method is the first to allow the determination of tobacco biomarkers in oral fluid using dried saliva spots, which is considered a sensitive, simple and low-cost alternative to conventional methods.
Keywords: Dried saliva spots; Oral fluid; Gas chromatography-tandem mass spectrometry; Nicotine; Biomarkers of tobacco